Exploring the Impact of the Internet Age on International Politics - Hu, Ruochen (Transactions on Social Science, Education and Humanities Research, 2023)
At the beginning of the 21st century, with the deepening development of the wave of informationization, the world's countries are becoming more and more dependent on the Internet, and the international political efficacy of the information network is becoming more and more prominent in the field of global politics, economy, military and culture, and in addition to the impact of the network era on the international community and the global system, the network era has also become an important content of each country's competition for the dominance of the cyberspace to become the competition for the international political power, and at the same time, it has also had a deep impact on the public life in the network. At the same time, it has also had a deep impact on the public life in the network. In this paper, we will study the impact of the network era on international politics, explore how the network has an impact on international politics in all aspects, and have important theoretical and practical significance to enhance the relevant people's competition in cyberspace and its impact on their lives.